Implementasi Makna Immanuel dalam Bahasa Jawa dengan Konsep Makna “Manunggaling Kawula Gusti” dalam Islam Tasawuf - Firmansah, Endik; Simon, Simon (Melo: Jurnal Studi Agama-agama, 2023)
Abstract: The Javanese Bible has a slightly different translation from other translations for the meaning of the word Immanuel. In particular, this difference can be seen when comparing the meaning of Immanuel in Javanese and the meaning of Immanuel in Indonesian. What is interesting is that the translation in Javanese for the word Imanuel has similarities with the sentence "manunggaling kawula Gusti", which is a term that is very familiar in Sufism Islamic circles in Javanese society. The first question is whether the translation in Javanese is correct according to the original meaning or not. Second, is it true that the word Imanuel has similarities with the concept of "manunggaling kawula Gusti" in the Islamic belief in Sufism or not. Third, does the similarity of concepts also mean the same meaning? Fourth, with these similarities, the meaning of Immanuel in Javanese can be used as a means of cultural inculturation and contextualization of Islamic Sufism. Some of these questions will bring the discussion to a new insight related to the Christology of the meaning of Immanuel in the Javanese translation. This writing uses qualitative research methods, with a review of appropriate reference books and journals. Furthermore, it is also hoped that, by understanding the correct concepts and meanings, we can carry out cultural inculturation and contextualization appropriately in using the term Immanuel. Abstrak: Alkitab bahasa Jawa memiliki terjemahan yang sedikit berbeda dengan terjemahan lain untuk makna kata Imanuel. Secara khusus perbedaan tersebut terlihat ketika membandingkan antara arti Imanuel dalam bahasa jawa dan arti Imanuel dalam bahasa Indonesia. Menariknya adalah, terjemahan dalam bahasa Jawa untuk kata Imanuel memiliki kesamaan dengan kalimat “manunggaling kawula Gusti” yaitu istilah yang sangat familiar dalam kalangan Islam Tasawuf masyarakat Jawa. Pertanyaan pertama, apakah terjemahan dalam bahasa Jawa tersebut benar sesuai makna aslinya atau tidak. Kedua, apakah benar kata Imanuel memiliki kesamaan dengan konsep “manunggaling kawula Gusti” dalam keyakikan Islam Tasawuf atau tidak. Ketiga, apakah persamaan konsep tersebut juga berarti persamaan makna. Keempat, apakah dengan persamaan tersebut maka makna Imanuel dalam bahasa Jawa dapat dijadikan sebagai sarana inkulturasi budaya dan kontekstualisasi terhadap Islam Tasawuf. Beberapa pertanyaan ini, akan membawa pembahasan kepada sebuah wawasan baru terkait dengan Kristologi dari makna Imanuel dalam terjemahan bahasa Jawa. Penulisan ini menggunakan metode penelitian kualitatif, dengan tinjauan kepada buku dan jurnal referensi yang sesuai. Selanjutnya juga diharapkan, dengan pemahaman konsep dan makna yang benar, maka dapat melakukan inkulturasi budaya dan kontekstualisasi secara tepat dalam menggunakan istilah Imanuel.